PENGARUH MEDIA CONE TERHADAP KETERAMPILAN MOTORIK KASAR ANAK - Titin Kusayang (Jurnal Muara Olahraga, 2021)
Abstract The purposeof the researchistoseethe effect ofthe useof mediaconein gross motor skills of children inkindergarten Pembina Sungai Penuh. The method usedwas aquantitativeapproach, this study is a quasiexperimentaldesign. The research resultshows that thechildrenin theexperimental class usinconemediahavea highermeanthanthe control classthatusesthe string media. Based on thecalculation ofthe t-test showed thatt count is greaterthanttableshowsthatthere isa significant impact on gross motor skills of children. It can be concludedthat theuse ofmediacone has asignificant effect on gross motor skills of children inkindergarten Pembina Sungai Penuh. Keywords: Cone, Gross Motor, Skills